Circ-ZDHHC5 Accelerates Esophageal Squamous Cell Carcinoma Progression in vitro via miR-217/ZEB1 Axis - Wang, Qian; Yang, Lili; Fan, Yanxin; Tang, Weiwei; Sun, Handong; Xu, Zhipeng; Zhou, Jian; Zhang, Yanzhou; Zhu, Bin; Cao, Xiufeng (Frontiers in Cell and Developmental Biology, 2020)
Circular RNA (circRNA) exhibits a covalently closed circular conformation and is structurally stable. Nevertheless, the precise effects exerted by circRNA in esophageal squamous cell carcinoma (ESCC) remains uncertain. CircRNA was ascertained by human circRNA array study and confirmed by quantification of reverse transcriptase polymerase reactions. A luciferase reporter, fluorescence in situ hybridization experiment was exploited to explore the interaction between circ-ZDHHC5 and miR-217. The function of circ-ZDHHC5 was determined by siRNA-mediated knockout of circ-ZDHHC5 in vitro proliferation, migration and invasion. Circ-ZDHHC5, rather than liner ZDHHC5 mRNA, rose in ESCC patients’ tissues, plasma and ESCC cell lines in comparison with normal controls. Knockdown of circ-ZDHHC5 inhibited tumorigenesis in ESCC cells, and co-transfection of si-circ-ZDHHC5 and miR-217 mimics further enhanced above effect. Noticeably, the present study showed that circ-ZDHHC5 was miR-217 sponge to modulate the expression of zinc finger E-box binding homeobox 1 (ZEB1), further facilitating ESCC tumorigenesis. As revealed by this study, circ-ZDHHC5 can act as a new potential circular biomarker for detecting ESCC. It provides a novel perceptivity for the treatment of ESCC that circ-ZDHHC5 could impact on the ESCC progression by sponging miR-217 with ZEB1.